It’s All About Fishing: Robert Ellis Jenkins (1940-2023) and His Life Among Freshwater Fishes of Virginia and the Redhorse Suckers - Eric J. Hilton (Southeastern Fishes Council Proceedings, 2023)
Robert (Bob) Ellis Jenkins passed away in Salem, Virginia, on Wednesday, July 12, 2023. Bob was born February 9, 1940 in Brooklyn, New York. As a child, Bob took an early interest in natural history, and was a particularly avid fisherman. He attended Roanoke College (Salem, VA) as an undergraduate and entered into a Masters degree program at Virginia Tech (Blacksburg, VA), only to leave before finishing for a position at the NOAA Systematics Lab based at the Smithsonian Institution’s National Museum of Natural History. He eventually became faculty at his alma mater, Roanoke College, where he would spend virtually all of his career. It was at the Smithsonian that he began his lifelong friendship and collaboration with Ernie Lachner. He also met Edward Raney, who would become his Ph.D. advisor at Cornell University. Originally Bob was to work on the cyprinid genus Nocomis, but switched the focus of his dissertation to the catostomids of the genus Moxostoma. Bob published 38 peer-reviewed papers on a wide range of taxa (predominantly catostomids and leuciscids, but also ictalurids, percids, and centrarchids), as well as general zoogeography of fishes from the southeastern U.S. His research always emphasized taxonomy and distribution of fishes, but one of the roots of his love of this work on the diversity of fishes was his concern for the conservation of fishes and their habitats. Bob will perhaps be best remembered for his monumental book (with Noel Burkhead), The Freshwater Fishes of Virginia.
Keywords: obituary; biography; Catostomidae; Cyprinidae; Percidae